Electoral incentives for territorial representation in the European Parliament. Issue 2 (17th February 2022) - Chiru, Mihail
ABSTRACT: While many citizens are indifferent about the EU, most MEPs are invisible in national politics and European Parliament elections are not fought based on parliamentary activity records, some legislators still pursue territorial interests or foster constituency linkages. What explains such behavior? Drawing on written questions data from the 6th and the 7th terms of the European Parliament (EP) this article shows that despite the virtual absence of an electoral connection in EP elections, electoral system features, and electoral marginality influence the MEPs' engagement in geographical representation. Electorally marginal MEPs ask more questions on regional and national topics as do MEPs elected from STV systems. There is no evidence for a differential effect of district magnitude depending on ballot structure.